EFEKTIFITAS TEKNIK DISTRAKSI INTELEKTUAL DANRELAKSASI DALAM MENGURANGI INTENSITAS NYERI DISMENORE PADA SISWI KELAS VIII SMP NEGERI 1REMBANG KABUPATEN PASURUAN - Masruroh,; Ma’rifah, Asirotul (JURNAL KEPERAWATAN BINA SEHAT, 2014)
The most phenomena found in menstruation women is menstrual pain. Menstrual painthat interferesoftenmakeswomen, especiallyyoung women, doinga variety ofwaysto eliminate. The efforts to reduce pain caused by menstrual pain, among others with intellectual distraction and relaxation techniques. This research aimed to determine differences in the effectiveness of intellectual distraction techniques with relaxation techniques in reducing menstrual pain pain intensity on a class VIII student of Rembang 1 Junior High School Pasuruan District. This research uses the approach of true experimental pretest-posttest control group design. Its population is all class VIII student of Rembang 1 Junior High School Pasuruan District number 93 students. By using a quota sampling technique found 30 samples that met the research criteria. The results showed that intellectual distraction techniques are more effective than relaxation techniques in reducing menstrual pain intensity on a class VIII student Rembang 1 Junior High School Pasuruan District. Data analysis was by Wilcoxon statistical test results of α = 0.011 for intellectual distraction techniques, and α = 0.014 for relaxation techniques. With intellectual distraction techniques monopoly game, young women will feel happy, because it dissolves in the pleasure of playing so that the pain can be sidetracked.Keywords: effectiveness, intellectuals distraction techniques, relaxation techniques, menstrual pain intensity, teenage daughter